Effects of the head lift exercise and neuromuscular electrical stimulation on swallowing muscles activity in healthy older adults: a randomized pilot study - Poorjavad M (Dove Medical Press, 2019)
Marziyeh Poorjavad,1 Saeed Talebian Moghadam,2 Noureddin Nakhostin Ansari21Department of Speech Therapy, School of Rehabilitation, Isfahan University of Medical Sciences, Isfahan, Iran; 2Department of Physical Therapy, School of Rehabilitation, Tehran University of Medical Sciences, Tehran, IranPurpose: Swallowing physiology exhibits several changes in advanced ages. The present study aimed to investigate and compare effects of a period of the head lift exercise (HLE) and neuromuscular electrical stimulation (NMES) on swallowing muscles activity in healthy elderly.Patients and methods: A total of 23 older adults were randomized to either the HLE or NMES group for ten therapy sessions. They received pre- and post-therapy surface electromyography (sEMG) during water swallowing.Results: For the HLE group, duration of suprahyoid muscles activity was significantly reduced at post-intervention compared to pre-intervention (p=0.036). Moreover after treatments, duration and latency between onset and peak amplitude of suprahyoid muscles activity was significantly shorter in the HLE group compare to the NMES group (respectively, p=0.007 and p=0.003).Conclusion: Our findings suggest that the HLE, against the NMES, may be effective in reducing some aging effects on the suprahyoid muscles activity, especially in elders who demonstrate prolonged duration and latency between onset and peak of the suprahyoid muscles activity during swallowing.Keywords: deglutition, aging, electromyography, exercise, electric stimulation therapy